Psychometric Properties of the Iranian Version of the Behavioral Regulation in Exercise Questionnaire-2 (BREQ-2) - Alireza Hidarnia; Shamsaddin Niknami; Rabiollah Farmanbar; David Revalds Lubans (Tabriz University of Medical Sciences, 2011)
Background: The Behavioral Regulation in Exercise Questionnaire (BREQ) and the BREQ-2 are the most commonly used measures of behavioural regulation in exercise psychology. The purpose of the study was to assess the validity and reliability of the Iranian version of the BREQ-2 on a sample of university students.Methods: The BREQ-2 was translated into Persian by qualified experts and the psychometric properties of the instrument were assessed. Content validity was established, using a panel of 12 Iranian experts in the areas of health education, psychology, and exercise. Construct validity was assessed via confirmatory factor analysis (CFA), using LISREL 8.80 (N = 418). The reliability of the BREQ-2 was assessed, using a 2-week test-retest to establish its stability and Cronbach's Alpha to estimate its internal consistency.Results: The Iranian version of the BREQ-2 was slightly modified to improve content validity. Primary results of confirmatory factor analysis did not fully support the 5-factor uncorrelated model. The model was modified; and the fit indices indicated that the 5-factor correlated model was the best fit. The scale was found to have acceptable internal consistency (α > 0.7) and test-retest reliability (intra-class correlation coefficient [ICC] > 0.80).Conclusion: The Iranian BREQ-2 has acceptable validity and reliability in the study sample and may be used in relevant studies to assess behavioural regulation in similar samples.